Peranan Program Accurate Accounting Terhadap Efektivitas Pencatatan Laporan Penjualan Kredit - Yuliana, Hana; Triandi, Triandi (Institut Bisnis dan Informatika Kesatuan, 2013)
Accounting information systems is a very important thing in an enterprise to support theoperational activities and to make the process of identification and decision making easier. Inaddition accurate relevant, complete and on time information is one of vitalneeds of the enterprisein running business. The purpose of this research is to find out how a accurate program has animportant role relating to the effectiveness of credit sale report. By conducting this research, it’sexpected to provide advantage for all sides related, so that they see how the role of accurate programto the effectiveness of credit sale report. By conducting this research, it’s expected to provideadvantages for all sides related, so that they see how the role of accurate program to the effectivenessof credit sale report will be. The result of this research shows that an accurate program is able toincrease the quality of sale report information at PT. Golden Citra Dinamika. By certain speed,the time can be made thrifty in data input processing and report equipping, it can be gottenaccurate dara, the completeness of data yielded can meet the enterprise’s goal. The accurateprogram is able to facilitate operational process and make it more detail in presenting the report, sothe owners will be able to analyze all transactions clearly.